Rediseño del centro de reintegración con criterio holístico para mujeres jóvenes del cantón Quevedo - Pinos Tomala, Edgar Michael (2024)
A comprehensive approach addressing physical, mental, emotional and spiritual needs aimed at the female gender that I use the Re-design of the holistic reintegration center for young women of Canton Quevedo for the proposal of this current work. The aim of the project is to turn the center into a place that promotes the healing process through architecture, recognizing the importance of a suitable environment for recovery. To support a comprehensive perspective of reintegration, new recreational and therapeutic areas have been created within the project. In a coherent design that promotes emotional, mental and physical healing, spaces are proposed for individual and group therapies, meditation rooms, exercise areas.......